Pelatihan Pengembangan Pembelajaran Berdifrensiasi Bagi Guru di SD Negeri 2002005 Aek Tampang Kota Padangsidimpuan - Siti Maryam Pane; Helmalia Putri; Dalilah Amaliah Putri Lubis; Salman Alparis Sormin (Jurnal Transformasi Pendidikan Indonesia, 2024)
This training activity began with the problems faced by teachers at SD Negeri 2002005 Aek Tampang Padangsidimpuan City related to a lack of understanding of differentiated learning. As a result, the government's independent curriculum implementation policy has not run optimally. The aim of this training activity is to provide knowledge and skills in preparing and implementing differentiated learning. The method used in this service is the training and mentoring method. Participants in this training were 10 teachers, principals and school supervisors. Based on the results of the initial test data processing carried out before the training was carried out, information was obtained that 60% of the training participants were categorized as having sufficient understanding of differentiated learning. Furthermore, after the training there was an increase in knowledge and skills where 80% of the training participants were in the very good category in planning and implementing differentiated learning. So it can be concluded that through structured training and mentoring can improve teachers' skills in designing and implementing differentiated learning.